Characteristics of dogs and cats under surgical reproductive control registered in the Municipality of Los Olivos, Lima, Peru. Period 2015-2016 - Rojas V., Priscila (2019)
The aim of this study was to describe the demographic characteristics of the population of companion animals that underwent surgical reproductive control in the Municipality of Los Olivos (Lima, Peru) in the 2015-2016 period. The records of the Los Olivos Municipal Veterinary Clinic were reviewed by collecting information on the age, sex, species and address of the owner. The information was analyzed by descriptive statistics. Records of 140 dog and 155 cats were obtained. The average age of the dogs was 2.1 ± 1.5 (range: 8 months to 7 years) and of the cats was 1.2 ± 0.8 (range: 6 months to 4 years). The highest percentage of sterilizations corresponded to females in both species (90.7% in dogs and 89.0% in cats) and of mestizo phenotype (93.6% in dogs and 99.4% in cats). The area of ​​influence of the Municipal Veterinary Clinic of Los Olivos had a radius of up to 8.26 km. It is expected that the information will be useful to determine the target population of future neutering campaigns, as well as to plan logistics needs that will be required.